Thermal stability of modified end‐capped poly(lactic acid). Issue 22 (23rd June 2014) - Berger, Katrin; Gregorova, Adriana
ABSTRACT The influence of functional end groups on the thermal stability of poly(lactic acid) (PLA) in nitrogen‐ and oxygen‐enriched atmospheres has been investigated in this article using differential scanning calorimetry, thermogravimetric analysis (TGA), and dynamic mechanical analysis (DMA). Functional end groups of PLA were modified by succinic anhydride and l‐cysteine by the addition–elimination reaction. PLA was synthesized by azeotropic condensation of l‐lactic acid in xylene and characterized by nuclear magnetic resonance. The values of the activation energies determined by TGA in nitrogen and oxygen atmospheres revealed that the character of functional end groups has remarkable influence on the thermal stability of PLA. Moreover, DMA confirmed the strong influence of functional end groups of PLA on polymer chains motion. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 41105.